2019
DOI: 10.1021/acs.iecr.9b03182
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Remaining Useful Life in Cyclic Processes

Abstract: The analysis of remaining useful life (RUL) of systems and equipment enables the prevention of failures, so that effective maintenance can be performed in time to correct failures that are close to happening. The degradation signal of a variable can be used as a basis for estimating the RUL of a given system since this signal is modeled mathematically correctly. In this paper, the RUL of cyclic processes is analyzed with the determination of the number of remaining cycles (NRC) in order to maximize production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, it is feasible to use the ES method to smooth the original sensor parameters of 100 aeroengines. This method is a special weighted moving average method, where the current value can be regarded as a weighted average of the current actual value and the previous moment value [28]. The calculation is as follows:…”
Section: Exponential Smoothingmentioning
confidence: 99%
“…Therefore, it is feasible to use the ES method to smooth the original sensor parameters of 100 aeroengines. This method is a special weighted moving average method, where the current value can be regarded as a weighted average of the current actual value and the previous moment value [28]. The calculation is as follows:…”
Section: Exponential Smoothingmentioning
confidence: 99%
“…25 al. 22 demonstrated that this modeling could also be applied to adsorption systems. An industrially relevant number of cycles (>2000) could be used to validate these types of degradation models.…”
Section: Introductionmentioning
confidence: 98%
“…Ruthven reported up to four points over 725 cycles and Belding et al reported six data points over 50 000 cycles. With regards to the application of this data, De Marco et al recently used the Wiener process to estimate the remaining useful life of an absorbent material. The Weiner process is a degradation model, , which has typically been used to describe batteries after continuous charging and discharging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation